Physiological Adaptation of Limnobium laevigatum in Palm Oil Mill Effluent (POME) for Enhanced Phytoremediation Efficiency - Dahlia Wulan Sari; Widya Rahayu; Dwi Retna Kumalaningrum (Journal of Aquaculture Science, 2026)
The study aimed to evaluate a stepwise adaptation approach to improve process efficiency and operational resilience of Limnobium laevigatum in a palm oil mill effluent (POME) treatment system. The acclimatization treatments involved using POME concentrations of 50% and 75% for 6 days. The parameters observed were biomass productivity, morphological response, and levels of phosphate, nitrate, ammonia nitrogen, and chemical oxygen demand (COD). Through a gradual adaptation process, the system demonstrated significantly more stable performance. This is evident from biomass growth (71.0 ± 4.7%), the number of leaves (88.6 ± 2.8%), and shoot production (211.1 ± 19.2%). Although root length decreased by 38.0 ± 16.2% at a 75% concentration, L. laevigatum was still able to effectively filter pollutants. The removed pollutants included phosphate (23.7 ± 1.3%), nitrate (30.1 ± 8.1%), ammonia nitrogen (4.6 ± 1.9%), and COD (20.8 ± 2.3%). These findings indicate that multilevel adaptation enhances the treatment efficiency and operational resilience of L. laevigatum under high-concentration POME conditions. This approach provides a practical and scalable strategy for optimizing macrophyte-based wastewater treatment systems, particularly for agro-industrial wastewater rich in organic matter.